2022
DOI: 10.1111/aor.14391
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging during warm ex vivo kidney perfusion

Abstract: Background The shortage of donor organs for transplantation remains a worldwide problem. The utilization of suboptimal deceased donors enlarges the pool of potential organs, yet consequently, clinicians face the difficult decision of whether these sub‐optimal organs are of sufficient quality for transplantation. Novel technologies could play a pivotal role in making pre‐transplant organ assessment more objective and reliable. Methods Ex vivo normothermic machine perfusion (NMP) at temperatures around 35–37°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(81 reference statements)
0
8
0
1
Order By: Relevance
“…Even though MRI has shown promise for measuring renal physiological parameters during NMP, it is practical challenging, and therefore, new methods should be introduced. 27 We demonstrated that LSCI has potential for both renal cortex microperfusion visualization and quantification in human-sized kidneys. Thus, although further validation studies are needed LSCI is a promising technique for assessment of kidney viability during NMP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Even though MRI has shown promise for measuring renal physiological parameters during NMP, it is practical challenging, and therefore, new methods should be introduced. 27 We demonstrated that LSCI has potential for both renal cortex microperfusion visualization and quantification in human-sized kidneys. Thus, although further validation studies are needed LSCI is a promising technique for assessment of kidney viability during NMP.…”
Section: Discussionmentioning
confidence: 86%
“…To utilize NMP as a platform for continuous organ monitoring, there is a need for real time, non‐contacting, rapid, and sensitive technology suitable for real time assessment of renal overall vitality. Even though MRI has shown promise for measuring renal physiological parameters during NMP, it is practical challenging, and therefore, new methods should be introduced 27 . We demonstrated that LSCI has potential for both renal cortex microperfusion visualization and quantification in human‐sized kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…A fenti módszereken kívül számos egyéb lehetőség is felmerült, amelyek közül megemlítendő a képalkotó di agnosztika használata. Az első tanulmányok az MR spektroszkópia alkalmazásáról szóltak [54], legújabban pedig Schutter és mtsai [56] mutatták be eredményeiket ÖSSZEFOGLALÓ KÖZLEMÉNY sertés és humán vesék NMP alatti MRvizsgálatáról, amelynek során a szerkezeti analízisen kívül elemezték a regionális áramlási eloszlást, a metabolizmust, illetve kö vették a perfúzió alatt adott őssejtek útvonalát.…”
Section: Diagnosztikus Lehetőségekunclassified
“…25,26 Isolated perfused rat kidneys have been used in metabolism studies [27][28][29][30] for many decades but assessment of real-time metabolism by HP 13 C MR has only recently been reported in isolated perfused rat kidneys 31 and porcine kidneys. 32,33 However, HP 13 C MR studies are commonly performed in isolated perfused hearts [34][35][36] and livers. 37,38 We aimed to establish isolated perfused rat kidneys as an experimental model for evaluating the metabolism of HP 13 C substrates.…”
Section: Introductionmentioning
confidence: 99%
“…These preparations enable precise control over substrate compositions and concentrations, as well as pharmacological and physiological interventions 25,26 . Isolated perfused rat kidneys have been used in metabolism studies 27–30 for many decades but assessment of real‐time metabolism by HP 13 C MR has only recently been reported in isolated perfused rat kidneys 31 and porcine kidneys 32,33 . However, HP 13 C MR studies are commonly performed in isolated perfused hearts 34–36 and livers 37,38 .…”
Section: Introductionmentioning
confidence: 99%